PREVALENCE AND CORRELATES OF CONDOM ERRORS AMONG SEXUALLY ACTIVE RESIDENTS OF GEM SUB-COUNTY, SIAYA, COUNTY WESTERN KENYA, 2012-2014 - Barbara BURMEN (Rojan GÜMÜŞ, 2019)
Condom effectiveness is compromised by user errors. We set out to examine the rates of condom use and condom errors among sexually active persons living within a Health Demographic Surveillance this high HIV prevalence area in Western Kenya. We analyzed data from the second round of a longitudinal bio-behavioral survey that was conducted in Gem, Siaya County between November 2012 and February 2014.Logistic regression analysis was done to identify predictors of condom use among all sexually active persons and condom errors among participants reporting condom use in the past 3 months. Of 7815 persons interviewed minority (39%) reported having used male condoms with at least one sexual partner in the past 3 months of whom 459 (15%) reported condom errors. Majority of those reporting condom errors had experienced 'incomplete use' (i.e. (a combination of early removal, late application or both early removal and late application). Participants who had experienced condom errors were significantly more likely to be aged <25 years and 25-34 years compared to those who were aged 35 years and older (OR 1.5; 95% CI 1.1-1.9 and OR 1.3; 95% CI 1.0-1.8 respectively to have had 3 or more and 2 sexual partners in the past 12 months compared to those who had one (OR 2.4; 95CI 1.7-3.5 and OR 1.6;95%CI 1.2-2.1 respectively),to have reported their sex partners to have ever been drunk during sex (OR 1.7; 95% CI 1.1-2.7), to have used mind altering substances in the past 12 months compared to those who had never used mind altering substances in the past 12 months (OR 1.9; 95% CI 1.2-3.1), and to report that their sex partner had ever used mind altering substances in the past 12 months (OR 1.7; 95% CI 1.0-2.8). Limited experience with condom use and the use mind-altering substances may partly be responsible for condom errors. Sexual and reproductive health programs should provide health education to promote condom use and HIV risk awareness. Additional strategies to mitigate effects of drug abuse as a harm reduction strategy should be considered for HIV prevention.